Sexual Risk Behavior Among Virologically Detectable Human Immunodeficiency Virus-Infected Young Men Who Have Sex With Men. - Wilson, Patrick A; Kahana, Shoshana Y; Fernandez, Maria Isabel; Harper, Gary W; Mayer, Kenneth; Wilson, Craig M; Hightow-Weidman, Lisa B (JAMA pediatrics, 2015)
Human immunodeficiency virus (HIV) diagnoses continue to increase among young men who have sex with men (YMSM). Many YMSM living with HIV engage in sexual risk behaviors, and those who have a detectable viral load can transmit HIV to sex partners. Understanding factors that are related to sexual risk taking among virologically detectable (VL+) YMSM can inform prevention and treatment efforts.